Microstructure and Properties of β-TCP Reinforced Zn-Mg Matrix Composites - Yongjin HU; Wenxian WANG; Zeqin CUI (Taiyuan Ligong Daxue xuebao, 2022)
Pure zinc has good biocompatibility and moderate degradation rate, but its mechanical properties are not ideal, which limits its biomedical applications. In view of the poor mechanical properties of zinc and its alloys, high-energy ball milling and spark plasma sintering techniques were used to prepare the alloy with core-shell structure Zn-10Mg-xβ-TCP (x=0,1,3,5) composites, β-TCP was selected as the reinforcing phase to improve the mechanical and corrosion properties of pure zinc. The microstructure, mechanical properties, and corrosion properties of Zn-10Mg-xβ-TCP (x=0,1,3,5) composite materials were investigated. The results show that all samples are relatively dense at 95% or above. The micro/nano-mechanical hardness of Zn-10Mg-1β-TCP is significantly higher than that of other samples, reaching 4.008 GPa; compressive strength and bending strength are 397 MPa and 92 MPa, respectively, and elongation is 6.5%, This is due to the small addition of β-TCP which produces dispersion strengthening and dislocation strengthening. In the electrochemical experiment, the corrosion current of Zn-10Mg-1β-TCP is not much different from that of zinc-magnesium alloy, which is significantly higher than that of other samples; in the long-term immersion experiment, the average corrosion current of sample Zn-10Mg-1β-TCP is the largest and meets the degradation rate requirements of implant material.